Diagnostic efficacy of transperineal sonography in the verification of pelvic floor muscular and fascial defects. Case report - Mekan R. Orazov; Marina B. Khamoshina; Dianna A. Gevorgian (IP Berlin A.V., 2022)
Pelvic floor insufficiency (PFI) is one of the most common and understudied gynecological diseases. PFI is a major public health problem that will steadily increase due to population aging. The issues of early diagnosis remain unresolved. Physical examination remains the primary method of evaluating PFI, but manual examination alone is not enough to diagnose hidden pelvic floor (PF) defects. Topical verification of muscular and fascial PF defects is necessary to route patients for non-surgical or surgical treatment. 2D/3D transperineal sonography is a non-invasive, simple, and the most common method of imaging PF structures.